Cities and suburbs : an introduction to urban sociology - Choldin, Harvey M. (New York : McGraw Hill Education, 1985)
The book presupposes an exposure to introductory sociology concepts, such as primary group, bureaucracy, and stratification, which are usually taught in that course.
Chapter 1. The beginnings of urban sociology -- Chapter 2. An overview of the field -- Chapter 3. From nomadism to the medieval town -- Chapter 4. The rise of the industrial city -- Chapter 5. United states urbanization -- Chapter 6. Urban ecology: spatial differentiation -- Chapter 7. Residential differentiation -- Chapter 8. Blacks in the metropolis -- Chapter 9. The local community -- Chapter 10. Community life: recent concerns -- Chapter 11. Neighborhood change -- Chapter 12. Suburbanization and new metropolitan form -- Chapter 13. Suburban social life -- Chapter 14. Social networks -- Chapter 15. Slums: conditions and programs -- Chapter 16. Third-World urbanization.
Includes bibliographical references and index.
Keywords: SOCIOLOGY, URBAN